CIRCULATION IN BATHROOM TANNING TANNING INDUSTRIES WITHIN A CONTEXT OF CLEANER PRODUCTION - Salas Colotta, G. (2007)
The main objective of the project is to demonstrate the feasibility of recycling pickling-tanning baths, ensuring the quality of the final product at ali times and achieving, on the one hand, the reduction of saline pollution (50%) caused by pickling and tanning baths and, on the other hand, the reduction of chromium salt (14%) in tanning wastewater. With regards to the anatytical parameters of the bath, the results show that the parameters analysed (pH, conductivity, density, chlorides, sulphates, chrome, solids in suspension and fats) are stabilised and the values obtained do not imply interferences in the pickling-tanning process. In parallel to the execution of these analyses, physical and chemical tests for quality control of the leathers were carried out, both on wet-blue and crust leathers. The results showed that there were no significan! differences in the leathers obtained with recycled baths.